The impact of the private provision of WASH services on sustainable economic growth in sub-Saharan Africa - Nicholson, Michael (Advances in Social Sciences Research Journal, 2020)
This paper analyzes the expanded role of the private sector in the provision of water, sanitation, and hygiene (WASH) services in Africa. Since 2010, private capital has entered the WASH sector throughout the continent via innovative mechanisms such as municipal bonds and equity funds. The surge of capital has attempted to fill the $2.5 trillion annual investment gap that the United Nations (2014) estimates for key development sectors. A tension exists, however, between the private-sector-enabled provision of WASH services and key Sustainable Development Goals, particularly offering affordable water and ending chronic poverty. For example, the World Bank (2016) recently found that in countries that declare the right to “free” water, an underserved impoverished class often must pay a much higher price for water than the rich. The current analysis provides an empirical inquiry into the conditions under which the private sector is attracted to the provision of WASH services and estimates its subsequent impact on both economic growth and inclusive development.